The application of penalty charges in banking transactions "an Islamic view" - Bourega, Soufiane (s.n, 2012)
The study highlights the issue of penalty clause that is one of the controversial issues in the Islamic finance. Different opinions have been displayed by different scholars and researcher. The study uses the inductive method to collect the opinions on the issue of penalty clause. After analyzing the different views and the evidences, the study ended that the penalty clause can be included in some contracts such as manufacturing however the penalty clause cannot be a clause in contract of debts